Hybrid discrete-continuous model of invasive bladder cancer - Eugene Kashdan; Svetlana Bunimovich-Mendrazitsky (Mathematical Biosciences and Engineering)
Bladder cancer is the seventh most common cancer worldwide.Epidemiological studies and experiments implicated chemicalpenetration into urothelium (epithelial tissue surrounding bladder) inthe etiology of bladder cancer.In this workwe model invasive bladder cancer. This type of cancer starts in theurothelium and progresses towards surroundingmuscles and tissues, causing metastatic disease.Our mathematical model of invasive BC consists of two coupledsub-models: (i) living cycle of the urothelial cells (normal and mutated) simulatedusing discrete technique of Cellular Automata and (ii) mechanism oftumor invasion described by the system of reaction-diffusionequations. Numerical simulations presented here are in good qualitative agreementwith the experimental results and reproduce in vitroobservations described in medical literature.